2019
DOI: 10.1016/j.jmii.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections: Current status and associated risk factors among school aged children in an archetypal African urban slum in Nigeria

Abstract: Intestinal parasitic infections are very severe among school aged children in the urban slums, thus regular mass de-worming programs, health education, and the provision of safe drinking water is recommended to combat IPIs among the school aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
34
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 30 publications
13
34
2
3
Order By: Relevance
“…This nding was in line with the studies conducted in Kenya (43%) (53), Nigeria (42.6%) (54), and Palestine (32.0-41.5%) (55). On the other hand, studies that showed higher prevalence than our ndings were done in West Africa (63.1%) (56), South Africa (68%) (57), Tanzania (63.91%) (58), Nigeria (67.4%) (59,60), and Mkhanyakude District, Burkina Faso (84.7%) (61). However, our results were higher than the studies conducted in South Africa (37.5%) (62), Eastern Region of Nepal (31.5%) (63), Northwestern Iran (10.6%) (64), Tehran, Iran (18.4%) (65), and Yemen (31.8%) (66).…”
Section: Discussionsupporting
confidence: 92%
“…This nding was in line with the studies conducted in Kenya (43%) (53), Nigeria (42.6%) (54), and Palestine (32.0-41.5%) (55). On the other hand, studies that showed higher prevalence than our ndings were done in West Africa (63.1%) (56), South Africa (68%) (57), Tanzania (63.91%) (58), Nigeria (67.4%) (59,60), and Mkhanyakude District, Burkina Faso (84.7%) (61). However, our results were higher than the studies conducted in South Africa (37.5%) (62), Eastern Region of Nepal (31.5%) (63), Northwestern Iran (10.6%) (64), Tehran, Iran (18.4%) (65), and Yemen (31.8%) (66).…”
Section: Discussionsupporting
confidence: 92%
“…[1]. Compared to age groups, hookworm infection has been found highest for older age groups (>12 years) than lower age groups (Table 2), which agrees with other studies [6, 26,31]. For instance, Hotez and Kamath [6] mentioned that hookworm infection has steadily raised in the intensity during late childhood with either a peak or a plateau in adulthood.…”
Section: Discussionsupporting
confidence: 84%
“…27 A study conducted in Nigeria and Nepal also revealed that A. lumbricoides was one of the dominant species. 24,30 In the study area, there was no significant sanitation and personal hygiene problem that could be probable reasons for the low prevalence of Ascaris infections. Most children did not defecate in open field since they had sufficient latrine facilities in their home.…”
Section: Discussionmentioning
confidence: 94%
“…29 A higher overall prevalence of IPI was also reported from different parts of Africa. 30,31 This might be due to differences in environmental and socioeconomic conditions, variations in method of diagnosis and community awareness. A huge variation in the sensitivity of wet mount, formol-ether concentration and Kato Katz tests in the diagnosis of intestinal parasites was documented.…”
Section: Discussionmentioning
confidence: 99%